Neurological events reported after COVID-19 vaccines: an analysis of vaccine adverse event reporting system - Frontera, Jennifer A.; Tamborska, Arina A.; Doheim, Mohamed F.; Garcia-Azorin, David; Gezegen, Hasim; Guekht, Alla; Yusof Khan, Abdul Hanif Khan; Santacatterina, Michele; Sejvar, James; Thakur, Kiran T.; Westenberg, Erica; Winkler, Andrea S.; et al. (John Wiley & Sons, 2022)
Objective: To identify the rates of neurological events following administration of mRNA (Pfizer, Moderna) or adenovirus vector (Janssen) vaccines in the U.S. Methods: We used publicly available data from the U.S. Vaccine Adverse Event Reporting System (VAERS) collected between January 1, 2021 and June 14, 2021. All free text symptoms that were reported within 42 days of vaccine administration were manually reviewed and grouped into 36 individual neurological diagnostic categories. Post-vaccination neurological event rates were compared between vaccine types and to age-matched baseline incidence rates in the U.S. and rates of neurological events following COVID. Results: Of 306,907,697 COVID vaccine doses administered during the study timeframe, 314,610 (0.1%) people reported any adverse event and 105,214 (0.03%) reported neurological adverse events in a median of 1 day (IQR0-3) from inoculation. Guillain-Barre Syndrome (GBS), and cerebral venous thrombosis (CVT) occurred in fewer than 1 per 1,000,000 doses. Significantly more neurological adverse events were reported following Janssen (Ad26.COV2.S) vaccination compared to either Pfizer-BioNtech (BNT162b2) or Moderna (mRNA-1,273; 0.15% vs 0.03% vs 0.03% of doses, respectively, p < 0.0001). The observed-to-expected ratios for GBS, CVT and seizure following Janssen vaccination were ≥1.5-fold higher than background rates. However, the rate of neurological events after acute SARS-CoV-2 infection was up to 617-fold higher than after COVID vaccination. Interpretation: Reports of serious neurological events following COVID vaccination are rare. GBS, CVT and seizure may occur at higher than background rates following Janssen vaccination. Despite this, rates of neurological complications following acute SARS-CoV-2 infection are up to 617-fold higher than after COVID vaccination. ANN NEUROL 2022;91:756–771.